2021
DOI: 10.1371/journal.pone.0248542
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in underserved communities of North Carolina

Abstract: Background In the United States, underserved communities including Blacks and Latinx are disproportionately affected by COVID-19. This study sought to estimate the prevalence of COVID-19 vaccine hesitancy, describe attitudes related to vaccination, and identify correlates among historically marginalized populations across 9 counties in North Carolina. Methods We conducted a cross-sectional survey distributed at free COVID-19 testing events in underserved rural and urban communities from August 27 –December 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 32 publications
6
63
1
Order By: Relevance
“…The finding that individuals of Black or African American race are less likely to obtain the COVID-19 vaccine is not surprising. In fact, our finding is consistent with the literature for both the COVID-19 vaccine and for the seasonal influenza vaccine [ 15 , 16 , 17 , 20 ]. In a study of 948 persons from North Carolina, individuals who identified as Black were more likely to be COVID-19 vaccine-hesitant than compared to the referent group (OR: 1.69, p = 0.002, 95% CI: 1.16, 2.45) [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding that individuals of Black or African American race are less likely to obtain the COVID-19 vaccine is not surprising. In fact, our finding is consistent with the literature for both the COVID-19 vaccine and for the seasonal influenza vaccine [ 15 , 16 , 17 , 20 ]. In a study of 948 persons from North Carolina, individuals who identified as Black were more likely to be COVID-19 vaccine-hesitant than compared to the referent group (OR: 1.69, p = 0.002, 95% CI: 1.16, 2.45) [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, our finding is consistent with the literature for both the COVID-19 vaccine and for the seasonal influenza vaccine [ 15 , 16 , 17 , 20 ]. In a study of 948 persons from North Carolina, individuals who identified as Black were more likely to be COVID-19 vaccine-hesitant than compared to the referent group (OR: 1.69, p = 0.002, 95% CI: 1.16, 2.45) [ 20 ]. In a study of seasonal influenza among health care workers, non-Hispanic blacks had lower uptake of vaccination than non-Hispanic whites based on a total direct effect (PR = 0.87; 95% CI = 0.75, 0.99) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…( Ruiz and Bell, 2021 , Malik et al, 2020 , Shaw et al, 2021 ) However, females were associated with 1.3 to 2.5 times the odds of being COVID-19 vaccine hesitant when compared to males after adjusting for multiple covarites. ( Daly and Robinson, 2021 , Latkin et al, 2021 , Callaghan et al, 2021 , Coe et al, 2021 , Tram et al, 2021 , Khubchandani et al, 2021 , Doherty et al, 2021 , Nikolovski et al, 2021 , Halbrook et al, 2021 , Garcia et al, 2021 )…”
Section: Resultsmentioning
confidence: 99%
“…This hesitancy in communities of color could be explained by past and present experiences and distrust of the healthcare and criminal systems, lack of adequate access to regular healthcare, transportation and language barriers, and the disproportionate burden of this pandemic [ 28 , 29 ]. A recent study of attitudes related to vaccination among racial minority and marginalized populations across nine counties in NC [ 30 ] found that factors associated with hesitancy in multivariable logistic regression included being female, being Black, calendar month, safety concerns, and government distrust [ 30 ]. To address vaccine hesitancy, particularly among minority populations, a multifaceted strategy prioritizing community engagement and considering people’s experiences must be employed [ 28 ]…”
Section: Discussionmentioning
confidence: 99%